0299 Effect of Glycemic Extremes on Sleep/wake and Alzheimer's Disease Pathophysiology. (12th April 2019) - Carroll, Caitlin M; Stanley, Molly; Rubinow, David; Golias, Charlotte; Holtzman, David M; Macauley, Shannon L
Abstract: Introduction: Type 2 diabetes increases the risk of developing Alzheimer's disease by 2-4-fold. Further, sleep disruption is characteristic of both Alzheimer's disease and metabolic dysfunction. It remains unclear, however, how alterations in peripheral and brain metabolism alter pathology and, ultimately, impact the sleep/wake cycle. The goal of this study, therefore, was to elucidate how the brain regulates metabolism in euglycemic conditions, as well as when challenged with hyper- and hypoglycemic conditions, with the hypothesis that altered glucose homeostasis and sleep dysregulation may be leading to accelerated disease progression. Methods: Biosensors were implanted bilaterally into the hippocampus of APP/PS1 mice, a model of amyloid-beta (Aβ) overexpression, to measure ISF fluctuations in glucose, glutamate, and lactate. These were paired with cortical EEG and EMG recordings for simultaneous sleep/wake analysis. To examine the effect of glycemic extremes on the brain's metabolic profile and arousal state, the mice were challenged with a 2g/kg IP injection of glucose, a 1mg/kg IP injection of glibenclamide, a KATP channel antagonist, as well as a .5U/kg injection of insulin. Results: Both hyper- and hypoglycemic challenges result in significant increases in arousal in 3-month old, wildtype mice. This increased arousal matched the increases in ISF lactate, indicating an increase in overall neuronal activity. However, in an aged APP/PS1 model mouse, the metabolic response to glycemic challenges was muted and there was seemingly no impact on arousal state, which is likely due to an increase in the overall amount of time spent awake. This finding is consistent with previous data demonstrating progressive age and pathology-dependent increases in arousal time. Conclusion: This study represents a novel approach to understanding the interactions between sleep, cerebral metabolism, and Alzheimer's Disease progression. The results show both glycemic extremes and Alzheimer's Disease pathophysiology can cause increased arousal, which is known to further contribute to metabolic dysregulation, accelerate amyloid-beta and tau deposition and neurodegeneration, suggesting a cyclic relationship between sleep and disease pathology. Support (If Any): Harold and Mary Eagle Fund for Alzheimer's Research, NIH/NIA 1K01AG050719, New Vision Award through Donors Cure Foundation